STRETEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI DEKADENSI MORAL SISWA DI SMAN 1 DEMPET - Safitri, Dewi; Partono, Partono (Tarbawi : Jurnal Pendidikan Islam, 2023)
This study aims to determine: 1) Forms and factors that cause student moral decadence at SMAN 1 Dempet. 2) PAI teacher's strategy in overcoming the moral decadence of students at SMAN 1 Dempet. 3) Supporting and inhibiting factors for PAI teachers in overcoming moral decadence at SMAN 1 Dempet. This research includes field research using a qualitative approach. The data collection techniques were obtained from nonparticipant observation, interviews, and documentation. While the analysis of this research data includes data reduction, data presentation and drawing conclusions. The results of this study indicate that 1) The forms of student moral decadence that occur at SMAN 1 Dempet are truancy, cheating, dating, coming late to school, not attending midday prayers in congregation, cell phone abuse, smoking, drinking and playing playing cards accompanied by gambling. While the factors that cause student moral decadence are caused by several factors, including factors from themselves, family factors, school environment factors, community factors and technological factors. 2) The PAI teacher's strategy in overcoming student moral decadence is carried out by working with school stakeholders, giving advice, home visits, imposing sanctions and taking preventive measures. 3) Supporting factors for PAI teachers in overcoming student moral decadence, namely the existence of adequate facilities and infrastructure, then extracurriculars related to religion and good cooperation between fellow teachers. While the inhibiting factors are the lack of supervision and guidance from parents, the factor during the pandemic and the lack of understanding of Islam in students.